Nessus, Snort, & Ethereal power tools customizing open source security applications - Archibald, Neil (Jay Beale's open source security series, 2005)
Covers customizing Snort to perform intrusion detection and prevention; Nessus to analyze the network layer for vulnerabilities; and Ethereal to sniff their network for unusual traffic. This book describes the important concepts of coding and customizing tools, and provides readers with working scripts